Impact of Soil-Applied Humic Ameliorative Amendment on the Ligno-Cellulose Quality and Calorific Value of Switchgrass Panicum virgatum L. - Štefan Tóth; Božena Šoltysová; Štefan Dupľák; Pavol Porvaz (Agronomy, 2023)
The main objective of the paper was to determine the ligno-cellulose quality and calorific value of switchgrass Panicum virgatum L. The impact of nutrition treatments (pre-sowing soil humic amendment HA and/or NPK, with annual dose of N on both the treatments, and untreated control UC) and years were evaluated as main effects within a pilot experiment with seven cultivars tested during 2018–2022. Two data sets of acid detergent fiber (ADF), acid detergent lignin (ADL), crude cellulose (CE), hemicellulose (HEM), neutral detergent fiber (NDF), and high heating value (HHV) were evaluated, the primary one in terms of quality content and the secondary one in terms of quality yield. The average ADF content of the switchgrass was 43.94% (range 30.15–50.91), while the average contents of ADL, CE, HEM, NDF, and HHV were 9.21% (6.02–12.41), 34.73% (17.98–40.08), 30.49% (21.34–38.41), 74.43% (59.20–81.15%), and 17.206 kJ g−1 (16.579–17.799), respectively. An adequate value of ADF yield was 4.17 Mg ha−1 (0.01–29.31), while for ADL, CE, HEM, NDF and HHV this was 0.79 Mg ha−1 (0.00–5.39), 3.37 Mg ha−1 (0.01–23.92), 2.79 Mg ha−1 (0.01–17.66), 6.96 Mg ha−1 (0.01–46.93), and 1.466 hGJ ha−1 (0.003–10.603), respectively. In terms of the both quality sets the cultivar was confirmed to be the most important factor followed by the year, with nutrition having the least impact. This impact order of the main effects was valid for each of the parameters. Moreover, in terms of quality yield the formation of homogeneity groups corresponded with dry matter yield and therefore with the order of cultivars (EG 1101 ˃ BO Master ˃ EG 1102 ˃ Kanlow ˃ Alamo ˃ Carthage ˃ NJ Ecotype), the years (2021 ˃ 2020 ˃ 2022 ˃ 2019 ˃ 2018), and the treatments (HA ˃ NPK ˃ UC).